2022
DOI: 10.3847/1538-4357/ac34f1
|View full text |Cite
|
Sign up to set email alerts
|

Circumnuclear Dust in AP Librae and the Source of Its VHE Emission

Abstract: The broad high-energy spectral component in blazars is usually attributed to various inverse Compton scattering processes in the relativistic jet, but has not been clearly identified in most cases due to degeneracies in physical models. AP Librae, a low-synchrotron-peaking BL Lac object (LBL) detected in 2015 by H.E.S.S. at very high energies (VHE; >0.5 TeV), has an extremely broad high-energy spectrum, covering ∼9 decades in energy. Standard synchrotron self-Compton models generally fail to reproduce the V… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…The data were checked for radio frequency interference and then calibrated using VLBARUN (the Astronomical Image Processing System VLBA pipeline ;Greisen 1990). The imaging and analysis of source structure were done using a custom version of DIFMAP (Shepherd et al 1994): ngDIFMAP (Roychowdhury et al 2023). The best model (as discussed in Laha et al 2022 for a previous VLBA observation), as determined by the reduced chisquared value, is a PS centered on a uniformly bright disk.…”
Section: Vlbamentioning
confidence: 99%
See 1 more Smart Citation
“…The data were checked for radio frequency interference and then calibrated using VLBARUN (the Astronomical Image Processing System VLBA pipeline ;Greisen 1990). The imaging and analysis of source structure were done using a custom version of DIFMAP (Shepherd et al 1994): ngDIFMAP (Roychowdhury et al 2023). The best model (as discussed in Laha et al 2022 for a previous VLBA observation), as determined by the reduced chisquared value, is a PS centered on a uniformly bright disk.…”
Section: Vlbamentioning
confidence: 99%
“…The details of the procedure are as given in Laha et al (2022), and Table 3 lists the details of the PS and extended disk that were found to describe the source best. We used Monte Carlo simulations (e.g., Briggs 1995;Chael et al 2018;Roychowdhury et al 2023) to verify that the extended emission around the PS is intrinsic to the source and is not an artifact of interferometric errors. In Table 4, we list the ratio of the core radio flux density to the 2-10 keV flux (also known as the Güdel-Benz, or GB, relation;Güdel & Benz 1993).…”
Section: Vlbamentioning
confidence: 99%
“…We also point out that we have terminated our jet calculation at 100 pc, even though the emission of more distant jet regions may also be important (e.g. Zacharias & Wagner 2016 ;Roychowdhury et al 2022 ).…”
Section: S U M M a Ry A N D O U T L O O Kmentioning
confidence: 99%
“…Collaboration 2020 ) indicates the presence of highly energetic particles on vast jet scales. Another interesting example is the blazar AP Librae, where the γ -rays cannot be successfully reproduced within a leptonic one-zone model requiring the need of an extended jet component to explain the γ -ray spectrum (Hervet, Boisson & Sol 2015 ;Zacharias & Wagner 2016 ;Roychowdhury et al 2022 ). In turn, the one-zone model is a bad approximation for these resolved structures.…”
Section: Introductionmentioning
confidence: 99%
“…This includes the addition of nine X-ray jets for which we have already published the Fermi/LAT analysis(Meyer & Georganopoulos 2014;Meyer et al 2015;Breiding et al 2017;Meyer et al 2019;Roychowdhury et al 2022) …”
mentioning
confidence: 99%